2014
DOI: 10.1016/j.bmc.2014.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Binding free energies for nicotine analogs inhibiting cytochrome P450 2A6 by a combined use of molecular dynamics simulations and QM/MM-PBSA calculations

Abstract: Molecular dynamics (MD) simulations and hybrid quantum mechanical/molecular mechanical (QM/MM) calculations have been perforemd to explore the dynamic behaviors of cytochrome P450 2A6 (CYP2A6) binding with nicotine analogs (that are typical inhibitors) and to calculate their binding free energies in combination with Poisson-Boltzmann surface area (PBSA) calculations. The combined MD simulations and QM/MM-PBSA calculations reveal that the most important structural parameters affecting the CYP2A6-inhibitor bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…We used this approach to estimate binding of ligands to cathepsin B, but found that QM/MM-PBSA energies ( r 2 = 0.59) were worse than gas-phase QM energies ( r 2 = 0.80) [85] . However more recently, accurate QM/MM-PBSA results have been obtained for cytochrome P450 [86] , showing that performance depends on the system.…”
Section: Replacing MM With Qmmentioning
confidence: 99%
“…We used this approach to estimate binding of ligands to cathepsin B, but found that QM/MM-PBSA energies ( r 2 = 0.59) were worse than gas-phase QM energies ( r 2 = 0.80) [85] . However more recently, accurate QM/MM-PBSA results have been obtained for cytochrome P450 [86] , showing that performance depends on the system.…”
Section: Replacing MM With Qmmentioning
confidence: 99%
“…Zhan and co-workers have used a similar approach for metalloenzymes. They combined pseudobond QM/MM energies with PBSA solvation, using RESP charges from the QM/MM calculation, and an entropy term from a simple count of the number of rotable bonds lost during the binding and the number of water molecules displaced by the ligand. They used the B3LYP density functional with either the 6-31G* or 6-31+G* basis set for the ligand and the metal ion(s), together with their first-sphere ligands, as well as a few nearby residues.…”
Section: End-point Approachesmentioning
confidence: 99%
“…Their analysis showed that BPA-A was the strongest binder to the receptor (Starovoytov et al, 2014 ). Other similar studies include globin, for its catalytic mechanism in the hydrolysis of substituted phenyl hexanoates (Ercan et al, 2014 ), the role of conserved residues in substrate binding to Brassica rapa auxin amidohydrolase (Smolko et al, 2016 ), the effect of hydrophobic interactions in substrate binding to recombinant enzyme carboxylesterase (Shao et al, 2014 ), the substrate-enzyme interactions of endo-1,4-β-xylanase (Zhan et al, 2014 ), azoreductase protein for the biodegradation of azo dyes (Dehghanian et al, 2016 ; Haghshenas et al, 2016 ), cytochrome P450 2A6 for nicotine addiction (Lu et al, 2014 ), Cel48F for producing bioethanol via fiber degradation (Qian M. D. et al, 2016 ), rubisco for biofuel production (Siqueira et al, 2016 ), streptavidin-biotin complex in biochemical sensing (Liu F. J. et al, 2016 ), sorotidine 5-monophosphate decarboxylase for its impressive rate enhancement (Jamshidi et al, 2014 ), tyrosyl-tRNA synthetases for genetic encoding of unnatural amino acids (Ren et al, 2015 ), T7 RNA polymerase for generating RNA labels (Borkotoky et al, 2016 ), AF9 in the YEATS family for the recognition of H3K9ac (Wang Q. et al, 2016 ), cysteine protease 1 precursor from Zea for the hydrolysate of corn gluten meal (Liu et al, 2014 ), folate receptor alpha for producing milk with high folate concentration (Sahoo et al, 2014c ), and both acid amido synthetase (Wang X. et al, 2015 ) and brassinosteroid (Lei et al, 2015 ) for plant growth.…”
Section: Applications Of Mmpbsamentioning
confidence: 99%